2021
DOI: 10.30595/cerie.v1i1.9486
|View full text |Cite
|
Sign up to set email alerts
|

Sifat Mekanis pada Kompon Karet Alam Variasi Campuran Serbuk Ban Bekas untuk Aplikasi Bantalan Mesin

Abstract: Rubber is a good material used for engine mounting because it has good elastic and damping properties. To obtain good mechanical and damping properties, fillers can be added such as carbon black, nylon powder and silica. In this study used used tire crumb as filler material. With the method of adding used tire powder 0 phr, 6 phr, 12 phr, 18 phr sequentially on natural rubber compound A, B, C, and D. Rubber compounds made in this process are tested to determine the mechanical properties and Dumping vibrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This is also because the WRTC used in this study was an inactive filler. An inactive filler will cause an increase in the hardness of the rubber, but it will decrease the tensile strength of the rubber [8]. This finding is consistent with previous research that found tensile strength to be inversely proportional to rubber hardness [9].…”
Section: Tensile Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…This is also because the WRTC used in this study was an inactive filler. An inactive filler will cause an increase in the hardness of the rubber, but it will decrease the tensile strength of the rubber [8]. This finding is consistent with previous research that found tensile strength to be inversely proportional to rubber hardness [9].…”
Section: Tensile Propertiessupporting
confidence: 91%
“…These results are consistent with previous research that found that adding waste of rubber tire crumb as an inactive filler increased the hardness of rubber. An inactive filler will cause an increase in the hardness of the rubber [8].…”
Section: Hardness (Shore A)mentioning
confidence: 99%
See 1 more Smart Citation